2019
DOI: 10.1088/1674-4527/19/2/30
|View full text |Cite
|
Sign up to set email alerts
|

The r-mode instability windows of strange stars

Abstract: With the constraint from gravitational wave emission of a binary merger system (GW170817) and two-solar-mass pulsar observations, we investigate the r-mode instability windows of strange stars with unpaired and color-flavor-locked phase strange quark matter.Shear viscosities due to surface rubbing and electron-electron scattering are taken into account in this work. The results show that the effects of the equation of state of unpaired strange quark matter are only dominant at low temperature, but do not have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…The r-mode instability (Andersson 1998;Friedman & Morsink 1998;Andersson & Kokkotas 1998;Ho & Lai 2000) can trigger the exponential growth of gravitational wave (GW) emission in rapidly rotating neutron stars through the Chandrasekhar-Friedman-Schutz mechanism (Chandrasekhar 1970;Friedman & Schutz 1978) if the GW growth rate is faster than its damping rate. Over the past two decades, significant efforts have been devoted to better understanding the r-mode instability and its damping mechanisms with many interesting findings (see, e.g., Madsen 2000;Yang et al 2011;Wen et al 2012;Vidaña 2012;Haskell et al 2012;Alford & Schwenzer 2014a,b;Idrisy et al 2015;Moustakidis 2015;Dai et al 2016;Papazoglou & Moustakidis 2016;Ofengeim et al 2019;Wang et al 2019;Krüger & Kokkotas 2020). In particular, it was found that the r-mode instability window (a region in the spin frequency versus temperature plane) in which the r-mode is unstable depends sensitively on the EOS of neutron-rich matter, especially its symmetry energy term which encodes the information about the energy cost to make nuclear matter more neutron-rich.…”
Section: Introductionmentioning
confidence: 99%
“…The r-mode instability (Andersson 1998;Friedman & Morsink 1998;Andersson & Kokkotas 1998;Ho & Lai 2000) can trigger the exponential growth of gravitational wave (GW) emission in rapidly rotating neutron stars through the Chandrasekhar-Friedman-Schutz mechanism (Chandrasekhar 1970;Friedman & Schutz 1978) if the GW growth rate is faster than its damping rate. Over the past two decades, significant efforts have been devoted to better understanding the r-mode instability and its damping mechanisms with many interesting findings (see, e.g., Madsen 2000;Yang et al 2011;Wen et al 2012;Vidaña 2012;Haskell et al 2012;Alford & Schwenzer 2014a,b;Idrisy et al 2015;Moustakidis 2015;Dai et al 2016;Papazoglou & Moustakidis 2016;Ofengeim et al 2019;Wang et al 2019;Krüger & Kokkotas 2020). In particular, it was found that the r-mode instability window (a region in the spin frequency versus temperature plane) in which the r-mode is unstable depends sensitively on the EOS of neutron-rich matter, especially its symmetry energy term which encodes the information about the energy cost to make nuclear matter more neutron-rich.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsars are highly magnetized and rapidly rotating neutron stars, providing us an opportunity to explore physics under extreme conditions (Deng et al 2020; Deng et al 2021; Shan 2023; Shan et al 2022; Wen et al 2021). The models of spin‐down, and magneto‐thermal evolutions of pulsars have been used by many authors (Kou et al 2019; Wang et al 2019; Wen et al 2022; Yan et al 2018a; Yan et al 2020; Yuan et al 2017) as a way of probing the internal composition of these objects. Such studies rely on the fact that the physical quantities relevant for the rotation instability and energy loss of pulsars (Gao et al 2017, 2021; Liu et al 2017; Liu & Liu 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the r-mode amplitude driven by emission of GWs is hindered by different kinds of viscous damping mechanisms [19,20], such as the shear and bulk viscosities. The shear viscosity due to layer surface rubbing and particle scattering determines the relaxation of momentum components perpendicular to the direction of fluid flow, which usually operates effectively at low temperatures [21].…”
Section: Introduction R R Rmentioning
confidence: 99%